1996
DOI: 10.1021/es9509036
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Biodegradation of Petroleum Hydrocarbons with Guanidinium Fatty Acids

Abstract: Bioremediation of hydrocarbon-contaminated soils is an attractive process for treating contaminated soils because it converts contaminants into harmless byproducts at low cost. However, the process is slow and typically requires months to years to reach regulated end points. In laboratory studies, we have been able to improve the process by adding selected guanidinium fatty acids to the contaminated soils. One of these materials, guanidinium cocoate, was synthesized from coconut acid and guanidine carbonate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Predictive models for estimating the extent of petroleum hydrocarbon biodegradation (268) and diffusion-controlled bioavailability of crude oil components (621) have been developed. Properly chosen chemical surfactants may enhance biodegradation (79,80,453,529,634). The efficiency of processes for degradation of hydrocarbons will also depend on the nature of the hydrocarbon-contaminated material, the environmental conditions, and the characteristics of the microbial population that is present.…”
Section: Treatment Of Contaminated Soils and Sludgesmentioning
confidence: 99%
“…Predictive models for estimating the extent of petroleum hydrocarbon biodegradation (268) and diffusion-controlled bioavailability of crude oil components (621) have been developed. Properly chosen chemical surfactants may enhance biodegradation (79,80,453,529,634). The efficiency of processes for degradation of hydrocarbons will also depend on the nature of the hydrocarbon-contaminated material, the environmental conditions, and the characteristics of the microbial population that is present.…”
Section: Treatment Of Contaminated Soils and Sludgesmentioning
confidence: 99%
“…By reducing interfacial tensions, surfactants can mobilize NAPLs (1). Surfactants can also affect natural microbial populations in the subsurface (4,12,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial populations proliferated with natural organics enhanced the degradation of two chloro-and a nitro-herbicides (Moorman et al 2001). Moreover, Nelson et al (1996) observed faster degradation of hydrocarbon in soil with the help of soap-like fatty acids.…”
Section: Introductionmentioning
confidence: 98%